2015
DOI: 10.1299/jamdsm.2015jamdsm0016
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic vibration-assisted machining of chemically strengthened glass with workpiece bending

Abstract: This paper deals with axial ultrasonic vibration-assisted machining with workpiece bending. It was proposed as a novel machining method for the reduction of the chippings at the machined holes during micro through-hole drilling of chemically strengthened glass. In micro through-hole drilling of chemically strengthened glass, machining accuracy and efficiency tend to be low because the material's high hardness and brittleness cause rapid tool wear and large chippings at the inlet and outlet of the machined hole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The developed model was verified by the experiments on alumina. Noma et al [ 15 ] demonstrated that the drilled hole quality, in terms of exit chip size, can be significantly improved by the application of the compressive stresses at the bottom surface of the rotary ultrasonic machined chemically strengthened glass. In another study, Nambu et al demonstrated that the ratio of the hole depth to drill diameter during micro hole drilling can be significantly increased by the application of ultrasonic vibrations to the drill tool [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The developed model was verified by the experiments on alumina. Noma et al [ 15 ] demonstrated that the drilled hole quality, in terms of exit chip size, can be significantly improved by the application of the compressive stresses at the bottom surface of the rotary ultrasonic machined chemically strengthened glass. In another study, Nambu et al demonstrated that the ratio of the hole depth to drill diameter during micro hole drilling can be significantly increased by the application of ultrasonic vibrations to the drill tool [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…For difficult-to-machining materials, especially for precision machining of the hard and brittle materials, Ultrasonic vibration milling reflects more benefits. Noma Kazuki proposed that the axial ultrasonic vibration-assisted machining with workpiece bending has the potential for achieving high-precision and high-efficiency machining for chemically strengthened glass [1].Zhang Chenglong established the Mathematical model for cutting force in rotary ultrasonic face milling of brittle materials in his paper [2]. Bulla B. studied influence on the ductile behaviour of binderless tungsten carbide applying ultrasonic assisted diamond turning [3].…”
Section: Introductionmentioning
confidence: 99%